Synthesis of tinidazole by condensation-oxidation sequence using MoO3/SiO2 bifunctional catalyst - Chandorkar, J. G.; Shubhangi B. Umbarkar; Rode, C. V.; Kotwal, V. B.; Dongare, Mohan K. (Catalysis Communications, 2007)
Antimicrobial drug, tinidazole has been synthesized by condensation of 2-methyl,5-nitro-imidazole and 2-ethyl-thio-ethanol over MoO3/SiO2 catalyst to obtain 1-(2-ethyl-thio-ethanol)-2-methyl-5-nitro-imidazole which is further oxidized using hydrogen peroxide using the same MoO3/SiO2 catalyst to obtain tinidazole. MoO3/SiO2 catalyst (20%), synthesized by sol-gel process showed the highest acid strength and was successfully demonstrated to catalyze both condensation and oxidation in the synthesis of tinidazole. Due to the bifunctional activity of the catalyst, the use of acetic acid for condensation step and tungstic acid or ammonium molybdate for oxidation step in the conventional synthesis of tinidazole could be eliminated, thus making it an environmentally benign process. The catalysts could be recycled five times without any appreciable loss in the conversion and selectivity showing the potential for. the use of MoO3/SiO2 as bifunctional catalyst for the production of this industrially important compound. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: antimicrobial drug; condensation; MoO3/SiO2; Oxidation; solid acid catalyst; tinidazole

Manufacturing of tinidazole by recovering and recycling catalyst - Dongare, Mohan K.; Chandorkar, J. G.; Rode, C. V. (Asian Journal of Chemistry, 2008)
In this paper, the recycle process of tungstic acid by recovering it from waste during the manufacture of tinidazole is described. The recovered tungstic acid gives desired quality and quantity of tinidazole.
Keywords: Recovery; tinidazole; tungstic acid

Recovery of ammonical salts from mother liquid of 2-methyl-5-nitroimidazole - Dongare, Mohan K.; Rode, C. V.; Chandorkar, J. G. (Asian Journal of Chemistry, 2008)
An attempt have been made to recover the ammonical salt (ammonium sulphate and ammonium nitrate) from the mother liquid of 2-methyl-5-nitroimidazole successfully.
Keywords: 2-methyl-5-nitroimidazole; ammonium nitrate; ammonium sulphate; Recovery